Comparison of contemporary staging systems for oropharynx cancer in a surgically treated multi‐institutional cohort. Issue 5 (28th December 2018) - Elicin, Olgun; Broglie, Martina A.; Fankhauser, Niklaus; Stoeckli, Sandro J.; Pasche, Philippe; Reinhard, Antoine; Bongiovanni, Massimo; Huber, Gerhard F.; Morand, Grégoire B.; Soltermann, Alex; Arnold, Andreas; Dettmer, Matthias S.; et al.
Abstract: Background: Between the publication of the Union of International Cancer Control staging system (UICC) 7th and 8th editions, other staging algorithms for oropharyngeal squamous cell carcinoma (OPSCC) were proposed from Radiation Therapy Oncology Group (RTOG), MD Anderson Cancer Center (MDACC), and Yale University. Methods: With C‐statistics, the above‐mentioned five staging algorithms were compared for overall and relapse‐free survival endpoints in a multi‐institutional cohort of OPSCC cases ( n  = 338) treated with primary surgery. Results: Pathological UICC 8th ed yielded the highest C‐indexes in the entire cohort and in the HPV− subset, whereas MDACC was superior for HPV+ OPSCC. RTOG was the simplest and holistic algorithm with a noninferior discriminatory power. Conclusion: UICC 8th ed, MDACC, and RTOG offer moderate and comparable efficacy for staging in this OPSCC patient cohort undergoing surgical treatment. Notable discrepancy between clinical and pathological UICC 8th ed algorithms poses potential concerns in diagnosis, treatment, research, and data management.